Cómo Se Está Abordando El Desarrollo De La Compresión Lectora En Estudiantes Regulares Y Con NEE Asociados O No A La Discapacidad, En La Ciudad De Quito-Ecuador - Maldonado Sánchez Yolanda del Pilar; María Julia Cabascango Sánchez; Delgado Lara Catherine Shadira; Andrade Rivera Guadalupe Esperanza (International Journal of Education, Teaching, and Social Sciences, 2022)
When we talk about reading comprehension, we talk about understanding what we read from a text, it allows us to be analytical, reflective and interact, it is very interesting, really, but in reality we understand what we read, in these moments that we are living the habit is strengthening of reading in students with or without special SEN. One of the problems of today that we find many anomalies, students do not understand what they read and we can say that they do not like reading since teachers and representatives find ourselves between a rock and a hard place. It is important to look for strategies to teach students to love reading and understand that a child who reads will in the future be an adult who thinks to do good with society as defined by complexity and complex thinking that both are related to improve to the investigation of science and to sensitize humanity and allows us to go further to discover that through reading there is a new world